2021
DOI: 10.3390/biomedicines9111671
|View full text |Cite
|
Sign up to set email alerts
|

Role of Enteric Glia as Bridging Element between Gut Inflammation and Visceral Pain Consolidation during Acute Colitis in Rats

Abstract: Acute inflammation is particularly relevant in the pathogenesis of visceral hypersensitivity associated with inflammatory bowel diseases. Glia within the enteric nervous system, as well as within the central nervous system, contributes to neuroplasticity during inflammation, but whether enteric glia has the potential to modify visceral sensitivity following colitis is still unknown. This work aimed to investigate the occurrence of changes in the neuron–glial networks controlling visceral perception along the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…As mentioned above, enteric glial cells, which become activated during colitis in rats [ 34 , 54 ], are able to modulate both neuronal and immune functions and participates in visceral sensitivity regulation [ 18 , 55 , 56 ] by modulating different pathways within the gut [ 27 , 57 ]. E. sativa treatment, turning off both glia and MCs signaling, could counteract the perpetuation and the amplification of the inflammatory response, promoting tissue healing and reducing chronic pain associated with colitis, as observed in our recent study [ 17 ]. Indeed, the treatment with E. sativa DSM significantly reduced the number of mast cells in the colon of DNBS animals, confirming the regulation of the immune response as one of the mechanisms by which E. sativa’s active components promote gut healing.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…As mentioned above, enteric glial cells, which become activated during colitis in rats [ 34 , 54 ], are able to modulate both neuronal and immune functions and participates in visceral sensitivity regulation [ 18 , 55 , 56 ] by modulating different pathways within the gut [ 27 , 57 ]. E. sativa treatment, turning off both glia and MCs signaling, could counteract the perpetuation and the amplification of the inflammatory response, promoting tissue healing and reducing chronic pain associated with colitis, as observed in our recent study [ 17 ]. Indeed, the treatment with E. sativa DSM significantly reduced the number of mast cells in the colon of DNBS animals, confirming the regulation of the immune response as one of the mechanisms by which E. sativa’s active components promote gut healing.…”
Section: Discussionmentioning
confidence: 52%
“…The present work is aimed at evaluating the therapeutic potential of E. sativa DSM in the management of the persistent visceral pain resulting from inflammatory damage to the colon. Colitis induced by 2,4-dinitrobenzenesulfonic acid (DNBS) injection in rats is indeed associated with the development of a visceral hypersensitivity that persists after colitis remission because of the establishment of concomitant alterations in the immune response, microbiota metabolism, nerve signaling, and glia function both in animals and humans [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, during inflammatory conditions, enteric glia surrounding neurons in the gut can undergo extensive changes which alter the interaction with the heterogenous cellular environment, contributing to perpetuating visceral hyperalgesia [ 50 , 51 , 52 , 53 ]. Enteric glia activation can be highlighted in animals and humans by changes in the expression of peculiar biological markers, such as GFAP [ 52 , 53 , 54 ]. In Figure 8 B, an up-regulation of GFAP expression in DNBS-treated rats with respect to controls (vehicle) can be observed.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the treatment with camelina was able to partially reduce the intestinal damage caused by colitis and strongly lower the number of mast cells infiltrating the tissue. This last parameter has high relevance in the context of visceral pain, which has been linked to a deregulation of mast cell function [ 52 , 53 , 71 , 72 ]. The control of mast cell activity is also important in the maintenance of gut homeostasis since these cells are the crossroads of many physiological processes playing a key role in the regulation of the intestinal barrier, secretion, and gut motility [ 48 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a recent report using a rat model of colitis induced by intracolonic 2,4-dinitrobenzene-sulfonic acid (DNBS), Lucarini et al [ 72 ] have demonstrated the essential role of enteric glia in the development of visceral hypersensitivity associated with intestinal inflammation. In this work, the gliotoxin fluorocitrate reduced intestinal damage and visceral sensitivity.…”
Section: The Enteric Nervous Systemmentioning
confidence: 99%